2021
DOI: 10.3389/fmicb.2021.733850
|View full text |Cite
|
Sign up to set email alerts
|

Localized Peptidoglycan Biosynthesis in Chlamydia trachomatis Conforms to the Polarized Division and Cell Size Reduction Developmental Models

Abstract: Cell size regulation in bacteria is a function of two basic cellular processes: the expansion of the cell envelope and its constriction at spatially defined points at what will eventually become the division plane. In most bacterial species, both cell wall expansion and restriction are dependent on peptidoglycan (PG), a structural polymer comprised of sugars and amino acids that imparts strength and rigidity to bacterial membranes. Pathogenic Chlamydia species are unique in that their cell walls contain very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The unusual process of cell division in Chlamydiaceae is initiated by a budding mechanism similar to that in FtsZ lacking Planctomycetes [ 22 ]. The asymmetric cell poles then mature into two approximately equally-sized daughter cells separated by an MreB-controlled septum containing a transient PGN ring which is remodeled during constriction and degraded afterwards [ 5 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unusual process of cell division in Chlamydiaceae is initiated by a budding mechanism similar to that in FtsZ lacking Planctomycetes [ 22 ]. The asymmetric cell poles then mature into two approximately equally-sized daughter cells separated by an MreB-controlled septum containing a transient PGN ring which is remodeled during constriction and degraded afterwards [ 5 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with MRY D2 inhibiting the formation of lipid I, PEN G acts downstream of MraY in the chlamydial PGN synthesis pathway (Figures 7 and 8). It binds to the transpeptidases PBP2 and PBP3 and the D,D-carboxypeptidase PBP6 [39,64], thereby inhibiting synthesis of cross-linked PGN and blocking cell division [36][37][38]. Although PEN G and MRY D2 both halt chlamydial cell division, different processes are likely to be involved at a cellular level in the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…PEN binds to penicillinbinding proteins (PBPs) and thereby interferes with the transpeptidation and remodeling of PGN, which is usually bactericidal in many bacteria via not fully understood cellular downstream effects. PEN acts bacteriostatically in Chlamydia and induces a reversible state of persistence by blocking cell division, which leads to the formation of enlarged ABs that persist within the host cell [14,[37][38][39]. Wolbachia, on the other hand, are unaffected by PEN treatment [40] but are susceptible to fosfomycin [32], which lacks activity against Chlamydia due to intrinsic resistance [41].…”
Section: Introductionmentioning
confidence: 99%
“…The septal disk expands to form a ring, which then constricts to finalize the division process. In C. trachomatis , penicillin binding protein 2 (PBP2) and PBP3 are two regulators which are independently responsible for the peptidoglycan ring expansion and constriction, respectively [ 83 , 84 ]. It has been observed that the volume and thickness of the ring decreases with the number of divisions that have occurred, resulting in smaller bacterial progeny size as infection time progresses.…”
Section: The Aberrant Body Morphology Induced By Iron Starvation Ifnγ...mentioning
confidence: 99%
“…Alternatively, peptidoglycan ring constriction can be inhibited by PBP3 inhibitors such as piperacillin. Broad spectrum β-lactamase inhibitors, like penicillin G, are able to target both PBP2 and PBP3 [ 83 , 84 ]. It is likely that a similar mechanism is present in the other members of the Chlamydiae phylum, as they all have homologs of PBP2 and PBP3 [ 73 ].…”
Section: The Aberrant Body Morphology Induced By Iron Starvation Ifnγ...mentioning
confidence: 99%